2016
DOI: 10.1155/2016/3062381
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Scheimpflug Imaging in Glaucoma Management: Current and Potential Applications

Abstract: Scheimpflug photography is the basis for a variety of imaging devices that are highly versatile. The applications of Scheimpflug imaging are wide in scope, spanning from evaluation of corneal ectasia to quantifying density in nuclear sclerotic cataracts. The potential uses for Scheimpflug-based devices are expanding and a number of them are relevant in glaucoma. In particular, they can provide three-dimensional image reconstruction of the anterior segment which includes assessment of the iridocorneal angle. Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…We used Scheimpflug imaging to measure anterior segment parameters, including ICA. In the literature, parameters obtained with Scheimpflug imaging have been shown to correlate well with gonioscopy, (25)(26)(27) and while Scheimpflug devices cannot directly visualize the angle, they have the advantage of producing 3-dimensional data to use in the analysis. Altan et al (28) found that in nonglaucomatous eyes with a preoperative open ICA, uneventful phacoemulsification reduced IOP, increased ACD, and widened the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…We used Scheimpflug imaging to measure anterior segment parameters, including ICA. In the literature, parameters obtained with Scheimpflug imaging have been shown to correlate well with gonioscopy, (25)(26)(27) and while Scheimpflug devices cannot directly visualize the angle, they have the advantage of producing 3-dimensional data to use in the analysis. Altan et al (28) found that in nonglaucomatous eyes with a preoperative open ICA, uneventful phacoemulsification reduced IOP, increased ACD, and widened the ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these data, the evaluation of the ACA with SP has some limitations when compared with AS-OCT, due to its inability to directly visualize the SS [19,86]. For this reason, Pentacam parameters show poor correlation with gonioscopy and UBM data in closed angles [87,88].…”
Section: Scheimpflug Photography (Sp)mentioning
confidence: 99%
“…An unquestioned advantage of AS-OCT and UBM over Sheimpflug imaging stems from the fact that the former two are suitable for direct visualization of the angle, ciliary body and sulcus [ 29 ]. While the abovementioned imaging methods are not essential to establish the diagnosis of iridoschisis, they may add to gonioscopy in the assessment of the iridocorneal angle.…”
Section: Clinical Characteristics and Diagnostic Imagingmentioning
confidence: 99%